2008
DOI: 10.1097/inf.0b013e31817acfaa
|View full text |Cite
|
Sign up to set email alerts
|

Human Bocavirus Infection in Children With Respiratory Tract Disease

Abstract: The difference observed in HBoV prevalence between children with RTD and controls provides support for a role of this virus in RTD. The frequent associations of HBoV with other respiratory viruses might be explained by the persistence of HBoV in the respiratory tract. The significance of HBoV viral load in nasopharyngeal secretions as a marker of pathogenicity merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
102
2
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 22 publications
16
102
2
7
Order By: Relevance
“…Also, we found that the longer hospitalization period was accompanied with high HBoV viral load patients and that was in agreement with Deng et al, (2012).These results suggest that HBoV is a significant pathogen in young children with ALRI that was underestimated in our region. We detected three NPA samples with HBoV positive PCR results that were accompanied by bacterial co-infection and were associated with low virus load that result was in agreement with Jiang et al, (2016) who reported that co-infection was more frequently found among patients with low virus load than those with high virus load suggesting HBoV as causative agent of ALRI, this results were in agreement with the studies of Brieu et al, (2008) and Kaida et al, (2010).…”
Section: Resultssupporting
confidence: 82%
“…Also, we found that the longer hospitalization period was accompanied with high HBoV viral load patients and that was in agreement with Deng et al, (2012).These results suggest that HBoV is a significant pathogen in young children with ALRI that was underestimated in our region. We detected three NPA samples with HBoV positive PCR results that were accompanied by bacterial co-infection and were associated with low virus load that result was in agreement with Jiang et al, (2016) who reported that co-infection was more frequently found among patients with low virus load than those with high virus load suggesting HBoV as causative agent of ALRI, this results were in agreement with the studies of Brieu et al, (2008) and Kaida et al, (2010).…”
Section: Resultssupporting
confidence: 82%
“…1). Previous studies detected HBoV mainly in children less than 5 years old and mostly in infants less than 2 years old (Choi et al, 2006;Kaplan et al, 2006;Kesebir et al, 2006;Kleines et al, 2007;Brieu et al, 2008;Canducci et al, 2008;Cilla et al, 2008). However, a recent report (Guido et al, 2011) and the present work confirm that HBoV1 is also a frequent virus in adults with respiratory disease.…”
Section: Resultscontrasting
confidence: 48%
“…21,27,28,64 Studies of nasopharyngeal samples have shown persistence of HBoV1 DNA for several months. [65][66][67][68] HBoV1 seroprevalence ranges from 25% in infants younger than 1 year to 93% and 100% in children of 3 (ref. 28) to 7 (ref.…”
Section: Discussionmentioning
confidence: 99%